GROWTH AND MINERAL COMPOSITION OF TROPICAL FORAGE LEGUMES INOCULATED WITH RHIZOBIA - Santos, Lucas Calazans; Venturini, Marcela Tonini; Pinheiro, Caroline de Morais; Gross, Eduardo (REVISTA DE AGRICULTURA, 2015)
The objective of this paper was to evaluate the influence of indigenous and inoculated rhizobia and ammonium sulfate fertilizer on growth and mineral composition ofÂ  the herbaceous legumes, Calopo (Calopogonium mucunoides), Ea Ea (Desmodium heterocarpon subsp. ovalifolium) and Kudzu (Pueraria phaseoloides), which are commonly used as forage plants and cover crops in Brazil. The treatments did not exhibit differences for total biomass of nodules. Lime application along with basic fertilization (without N) permitted nodulation and full growth and development of forages with native rhizobia.